Hybrid RANS/LES for active flow control. Issue 3 (29th April 2014) - Wang, Wei; Siouris, Spiridon; Qin, Ning
Abstract : Purpose: – The purpose of this article is to present numerical investigations of flow control with piezoelectric actuators on a backward facing step (BFS) and fluidic vortex generators on a NACA0015 aerofoil for the reattachment and separation control through the manipulation of the Reynolds stresses. Design/methodology/approach: – The unsteady flow phenomena associated with both devices are simulated using Spalart–Allmaras-based hybrid Reynolds averaged Navier-Stokes (RANS)/large eddy simulation (LES) models (detached eddy simulation (DES), delayed detached eddy simulation (DDES) and improved delayed detached eddy simulation (IDDES)), using an in-house computational fluid dynamics (CFD) solver. Results from these computations are compared with experimental observations, enabling their reliable assessment through the detailed investigation of the Reynolds stresses and also the separation and reattachment. Findings: – All the hybrid RANS/LES methods investigated in this article predict reasonable results for the BFS case, while only IDDES captures the separation point as measured in the experiments. The oscillating surface flow control method by piezoelectric actuators applied to the BFS case demonstrates that the Reynolds stresses in the controlled case decrease, and that a slightly nearer reattachment is achieved for the given actuation. The fluidic vortex generators on the surface of the NACA0015 case force the separated flow to fully reattach on the wing. Although skin friction is increased, there is a significant decrease in Reynolds stresses and an increase in lift to drag ratio. Originality/value: – The value of this article lies in the assessment of the hybrid RANS/LES models in terms of separation and reattachment for the cases of the backward-facing step and NACA0015 wing, and their further application in active flow control.